2018
DOI: 10.1159/000490084
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding: Beyond Nutrition

Abstract: In this article, we will summarize the key non-nutritional aspects of the introduction of complementary feeding. Intestinal maturation related to starch digestion is relatively complete by the time complementary feeding is recommended to be initiated. A much more complex maturation is needed, however, from the neurodevelopmental standpoint as the infants need to be able to hold their head and trunk and be able to coordinate tongue movement followed by swallowing. Issues can arise in infants with a history of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
19
0
2
Order By: Relevance
“…Evidence suggests that, if caregivers regularly feed infants in the absence of hunger and/or beyond their satiety, the infant's ability to eat in response to hunger and fullness cues may be undermined [101][102][103]. Consequently, a discordant chronic feeding response, with an inability to understand or misinterpretation of children's signals, easily leads to overfeeding and may contribute to weight gain and obesity, as well as to aggravate further problematic feeding behaviors [104].…”
Section: Responsive Feeding and Health Outcomes: Weight Gain And Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that, if caregivers regularly feed infants in the absence of hunger and/or beyond their satiety, the infant's ability to eat in response to hunger and fullness cues may be undermined [101][102][103]. Consequently, a discordant chronic feeding response, with an inability to understand or misinterpretation of children's signals, easily leads to overfeeding and may contribute to weight gain and obesity, as well as to aggravate further problematic feeding behaviors [104].…”
Section: Responsive Feeding and Health Outcomes: Weight Gain And Obesitymentioning
confidence: 99%
“…In addition, contexts in which the child can completely control the feeding situation (e.g., indulgent feeding), or the caregiver is completely uninvolved during meals (e.g., uninvolved feeding) are considered to be nonresponsive feeding practices [99]. Otherwise, a parent who allows the infant to determine timing, amount, and pacing of a meal helps the infant to develop self-regulation and secure attachment [104].…”
Section: Responsive Feeding and Health Outcomes: Weight Gain And Obesitymentioning
confidence: 99%
“…Complementary foods provide essential nutrients, but complementary feeding is also an important stage in the transition from milk feeding to family foods [6]. However, the introduction of complementary feeding requires an optimal level of physiological and neurological maturation for it to be successful [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An early orientation for parents is fundamental for the prevention of eating problems, thus avoiding the deficit of macronutrients. 5 The preference for sweet taste is common in this age group. This creates some problems, as these foods, in addition to having high caloric density, are usually poor in micronutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, children in the first years of life may have inadequate intake, both for more and less, of various nutrients, which will negatively influence their growth, neuropsychomotor development, immunity, in addition to metabolic imprinting. [6][7][8] In summary, it can be observed that the feeding of children in the first years of life has three topics that deserve special attention: 5,7,8 • Imbalance (for more or for less) of energy and protein supply; • Intake of various micronutrients below the recommendations: vitamins A, D, B12, C and folic acid; iodine; iron and zinc; • Low intake of omega 3 chain fatty acids, mainly Docosahexaenoic acid (DHA), with important consequences, not only for childhood, but throughout life, affecting growth, neurodevelopment, immunity and metabolic imprinting.…”
Section: Introductionmentioning
confidence: 99%